Corbyn: the strange rebirth of radical politics - Seymour, Richard (London, 2016)
"With a landslide in the first round, this unassuming antiwar socialist crushed the opposition, dealing a huge blow to the Blairite opposition. For the first time in decades, socialism is back on the agenda - and for the first time in Labour's history, it defines the leadership. This book tells the story of how Corbyn's rise was made possible by the long decline of Labour and a deep crisis in British democracy. It surveys the makeshift coalition of trade unionists, young and precarious workers, and students who rallied to Corbyn. It shows how a novel social media campaign turned the media's 'Project Fear' on its head, making a virtue of every accusation thrown at him. And finally it asks, with all the artillery that is still ranged against Corbyn, and given the crisis-ridden Labour Party that he has inherited, what it would mean for him to succeed."